Molecular Mechanisms of JNKs in anxiety and depression - Hillman, Pinja (My University, 2024)
Depression and anxiety disorders are among the most common causes of disability and suicide. The first hypothesis for depression was created approximately 70 years ago, indicating that the research behind the mechanism of mood disorders is relatively new. Depression and anxiety disorders are thought to be caused by the dysregulation of monoamines and significantly decreased levels of serotonin and norepinephrine in the brain. These monoamines have an essential role in regulating emotional and cognitive behaviour. Current antidepressants have been developed based on the monoamine hypothesis and have been shown to alleviate mood and increase adult neurogenesis, i.e., the formation of new neurons in the hippocampus. Neural cells formed in neurogenesis specialise, for example, to granule cells linked to memory formation and stress reactions. Impaired neurogenesis is thought to be connected to depression and anxiety. Other mechanisms behind mood disorders include dysregulation of the brain's inhibitory and exhibitory neurotransmitters, brain plasticity, and chronic stress. Recent studies have shown that the JNK (c-Jun N-terminal kinase) pathway is associated with controlling mood disorders. JNKs are intracellular kinases that control functions such as the brain's development, the death of nerve cells, and the state of inflammation in the brain. Research shows that the brain's JNK is linked to its plasticity and the emergence of new nerve cells in the hippocampus. Studies have investigated the effect of JNK on the emergence of depressive states and anxiety disorders. For instance, one study demonstrated that blocking JNK in the hippocampal granule cells during adulthood reduced anxiety—and depression-like symptoms in animal models. Furthermore, genetic irregularities within the JNK pathway have been linked to both schizophrenia and autism spectrum disorders. Addressing treatment-resistant depression poses a significant challenge, as one-third of current antidepressant users do not get a proper response to treatment. Consequently, new therapeutic approaches are essential to tackle this issue. Recent clinical trials have emerged with gamma- aminobutyric acid (GABA)- and glutaminergic neurotransmissions and psychedelic approaches. Furthermore, the current antidepressants do not target the activity of JNK. Thus, JNK or its downstream targets are valuable in drug development, as they may enable novel responses, especially in patients who do not benefit from existing drugs. However, further research is needed to confirm this hypothesis.

Masennus- ja ahdistuneisuushäiriöt ovat pitkään tunnistettuja ilmiöitä sekä yleisiä syitä työkyvyttömyydelle ja itsemurhille. Tutkimus mielenterveyshäiriöiden mekanismeista on kuitenkin verrattain uusi ilmiö, sillä ensimmäinen hypoteesi masennuksen mekanismista syntyi vasta noin 70 vuotta sitten. Masennus- ja ahdistuneisuushäiriöiden arvellaan johtuvan monoamiinien säätelyhäiriöstä ja merkittävästi alentuneesta serotoniinin ja noradrenaliinin pitoisuudesta aivoissa. Monoamiineilla on olennainen rooli emotionaalisen ja kognitiivisen käyttäytymisen säätelyssä. Nykyiset masennuslääkkeet on kehitetty monoamiinihypoteesin pohjalta ja niiden on osoitettu lievittävän mielialaa ja lisäävän aikuisiän neurogeneesiä eli uusien hermosolujen muodostumista hippokampuksessa. Neurogeneesissä syntyneet uudet hermosolut erikoistuvat esimerkiksi jyväissoluiksi, jotka toimivat muistinmuodostuksessa ja stressireaktioissa. Neurogeneesin heikentymisen ajatellaan olevan yksi mekanismeista masennuksen ja ahdistuksen taustalla. Muita tunnettuja taustamekanismeja ovat aivojen estävien ja kiihottavien välittäjäaineiden säätelyhäiriöt, aivojen plastisuus ja krooninen stressi. Eräs mielenterveyshäiriöihin liittyvä molekyyli, jota on hiljattain tutkittu, on JNK (c-Jun N-terminaalinen kinaasi). JNK:t ovat solunsisäisiä kinaaseja, jotka muun muassa säätelevät aivojen kehitystä, hermosolujen kuolemaa ja aivojen tulehdustilaa. Tutkimukset ovat osoittaneet, että aivojen JNK:t vaikuttavat aivojen plastisuuteen ja uusien hermosolujen syntymiseen hippokampuksessa, ja näissä tutkimuksissa on pääasiassa keskitytty JNK:n vaikutukseen masennustilojen ja ahdistuneisuushäiriöiden synnyssä. Esimerkiksi on osoitettu, että JNK:n estäminen aikuisiällä erikoistuneissa jyväissoluissa vähensi ahdistuksen ja masennuksen kaltaisia käyttäytymisiä eläinmalleissa. Lisäksi geneettiset poikkeavuudet JNK-reitillä on liitetty skitsofreniaan ja autismispektrin häiriöihin. Hoitoresistenttiin masennukseen puuttuminen on merkittävä lääketieteellinen haaste, sillä kolmasosa nykyisistä masennuslääkkeiden käyttäjistä ei saa asianmukaista vastetta hoitoon. Siksi onkin välttämätöntä kehittää uusia terapeuttisia lähestymistapoja. Viimeisimmissä kliinisissä tutkimuksissa on tarkasteltu gamma-aminovoihapon (GABA) ja glutamiinin neurotransmissiota ja psykedeelisten yhdisteiden käyttöä. Nykyiset masennuslääkkeet eivät myöskään suoraan kohdistu JNK:n toimintaan. Näin ollen JNK:t tai niiden reitin alavirran komponentit ovat potentiaalisesti arvokkaita kohteita lääkekehityksessä, sillä ne saattavat mahdollistaa uudenlaisia vasteita etenkin niillä potilailla, jotka eivät hyödy nykyisistä lääkityksistä. Tämän hypoteesin vahvistamiseksi tarvitaan kuitenkin lisätutkimuksia.
Keywords: Major Depressive Disorder, Anxiety disorder, Treatment-resistance, Neurogenesis, c-Jun N- terminal kinases, Granule cells.